The Effectiveness of Skills Education Programs in Enhancing the Economic Competitiveness of Generation Z: Efektivitas Program Pendidikan Keterampilan terhadap Peningkatan Daya Saing Ekonomi Generasi Z - Rismaya, Erin; Nasir, Abdul; Setiawan, Dadan (CV. Media Publikasi Profesional, 2025)
Generation Z, born between 1997 and 2012, faced unique challenges and opportunities in an increasingly competitive job market. Skills education programs were one solution to improve the economic competitiveness of this generation. This study aimed to examine the effectiveness of skills education programs in preparing Generation Z to compete in the workforce. Through quantitative methods, data were collected from 200 respondents who had participated in skills education programs at various institutions. The results showed that there was a significant positive relationship between skills education and increased economic competitiveness, with a p-value <0.05. This finding emphasized the importance of investing in skills education programs to prepare Generation Z to face challenges. This finding made a valuable contribution to the formulation of recommendations for future education policy development.